In the Search of Potential Serodiagnostic Proteins to Discriminate Between Acute and Chronic Q Fever in Humans. Some Promising Outcomes - Psaroulaki, Anna; Mathioudaki, Eirini; Vranakis, Iosif; Chochlakis, Dimosthenis; Yachnakis, Emmanouil; Kokkini, Sofia; Xie, Hao; Tsiotis, Georgios (Frontiers in Cellular and Infection Microbiology, 2020)
Coxiella burnetii is the causative agent of acute and chronic Q fever in humans. Although the isolates studied so far have shown that the two forms of the disease differ in virulence potential thus, implying a difference in their proteomic profile, the methods used do not provide sufficient discriminatory capability and often, human infections may be mis-diagnosed. The current study adds further knowledge to the results that we have already published on the Coxiella outer membrane protein 1 (Com1). Herein we identified the proteins GroEL, Ybgf, OmpH and UPF0422 as candidates for serodiagnostics of Q fever, cloned, expressed, purified and used them as antigens in ELISA. The proteins were then used for the screening of sera from patients suffering from chronic Q fever endocarditis, patients whose samples were negative for phase I IgG, patients whose at least one sample was positive for phase I IgG and patients suffering from various rheumatic diseases. Blood donors were used as the control group. We calculated sensitivity, specificity, positive predictive value, negative predictive value and Cohen’s kappa coefficient (κ) and we also performed binary logistic regression analysis to identify combinations of proteins with increased diagnostic yield. We found that proteins GroEL and Ybgf, together with Com1, play the most significant role in the correct diagnosis of chronic Q fever. Of these three proteins, it was shown that Com1 and GroEL present the highest sensitivity and specificity altogether. The results add to the existing knowledge that an antigen-based serodiagnostic test that will be able to correctly diagnose chronic Q fever may not be far from reality.